STRATEGI PENCAPAIAN KINERJA PEMASARAN MELALUI KEPUASAN PELANGGAN YANG DIMODERASI PEMASARAN DIGITAL PADA INDUSTRI KOSMETIK JAWA TIMUR - Johan Hari Sukwanto; Sukesi; Meithiana Indrasari (LPSDI Bina Patria, 2025)
The increasingly diverse development of cosmetic products is not fully followed by market growth, so companies need to understand the factors that influence marketing performance. This study aims to analyze the influence of market orientation, brand image, promotion, distribution, physical evidence, price, and product innovation on marketing performance through customer satisfaction, with digital marketing as a moderating variable. The study used a causal quantitative approach with a sample of 250 cosmetic consumers in East Java selected through purposive sampling. Data were collected using a questionnaire and analyzed using Partial Least Squares (PLS). The results show that market orientation, promotion, distribution, price, and product innovation have a significant influence on customer satisfaction, while brand image and physical evidence have no significant influence. Furthermore, brand image, physical evidence, and customer satisfaction have a significant influence on marketing performance, while the other variables do not show a direct effect. Customer satisfaction only mediates the relationship between product innovation and marketing performance, and digital marketing does not moderate the relationship between customer satisfaction and marketing performance